"Closer" or Context? Explaining Donald Trump's Relations with Congress. Issue 3 (30th August 2018) - Edwards, George C.
Abstract : Donald Trump entered office with aspirations for transformational policy change, much of which would have to be approved by Congress. Despite the president's many unique characteristics, we can employ the framework of the president's strategic position to explain his lack of success. The president's opportunity structure was mixed. He lacked an electoral mandate but was fortunate enough to serve in a unified government. Nevertheless, Republican cohesion was imperfect, partisan polarization was high, and there was little public pressure for Democrats to abate their strong opposition. The structure of most of the choices before Congress did not favor the president. As a result, he has not been successful in obtaining congressional support for most of his major initiatives. Making strategic assessments by asking a few key questions about the president's political environment provides us with crucial leverage for evaluating a president's likely success in obtaining the support of Congress for his initiatives.